PENGGUNAAN APLIKASI TIKTOK DALAM MENINGKATKAN PENGHASILAN MAHASISWA BERDASARKAN AKAD JU’ALAH - Pasi, Ida Royani (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2023)
This research aims to examine the practice of using the TikTok application among Hamzah Fansuri High School students in generating profits based on the Ju'alah agreement. Using the qualitative analysis method, namely conducting direct interviews with respondents to get answers to the problems studied. The number of respondents in this research were 10 active students at Hamzah Fansuri Subulussalam High School. After conducting interviews with 10 respondents, it was discovered that there was a practice of using the TikTok application to gain profits among Hamzah Fansuri Subulussalam High School students which was in accordance with the provisions of the Ju'alah agreement. Where in this Tiktok application there are jail parties and ma'jul parties (Tiktok perpetrators). Apart from that, in the Tiktok application there is also a ju'alah work object, where the ju'alah object in the Tiktok application is to download the Tiktok application, invite friends (new users) and watch videos. However, there are several things that must be taken into account that a person or new user is invited voluntarily, and not under intimidation from the inviting user. Furthermore, the videos or content viewed in the Tiktok application do not contain anything that violates the Sharia, such as videos that contain immoral elements, etc. that are prohibited by the Sharia.Keywords:  social media, tiktok, ju’alah